2012
DOI: 10.4049/jimmunol.1200662
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Clearance of Early Apoptotic Cells by Human Macrophages Requires M2c Polarization and MerTK Induction

Abstract: Mer tyrosine kinase (MerTK) is a major macrophage apoptotic cell (AC) receptor. Its functional impairment promotes autoimmunity and atherosclerosis, while overexpression correlates with poor prognosis in cancer. However, little is known about mechanisms regulating MerTK expression in humans. We found that MerTK expression is heterogenous among macrophage subsets, being mostly restricted to anti-inflammatory “M2c” (CD14+CD16+CD163+CD204+CD206+CD209−) cells, differentiated by M-CSF or glucocorticoids. Small numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
460
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(494 citation statements)
references
References 60 publications
28
460
2
4
Order By: Relevance
“…Monocytes conditioned with cmMTB differentiated into cells displaying an equivalent or low- er expression of M1 polarization markers (i.e., CD86, HLA-DR, FCAR and Serpine1) compared with cells differentiated in the presence of cmCTR (Supplementary information, Figure S1A-S1B). By contrast, the expression of markers related to M2 macrophage activation, such as CD16, CD163, MerTK, CD206, AMAC1 and CD200R1 [23][24][25][26][27], was upregulated in cmMTB-conditioned cells ( Figure 1B, Supplementary information, Figure S1B). Similarly, the expression of CCR2 and CCR5 chemokine receptors was higher in the presence of cmMTB, supporting the acquisition of the M2 program (Supplementary information, Figure S1C) [28,29].…”
Section: Differentiation Of Human Monocytes Towards An M2-like Activamentioning
confidence: 96%
See 2 more Smart Citations
“…Monocytes conditioned with cmMTB differentiated into cells displaying an equivalent or low- er expression of M1 polarization markers (i.e., CD86, HLA-DR, FCAR and Serpine1) compared with cells differentiated in the presence of cmCTR (Supplementary information, Figure S1A-S1B). By contrast, the expression of markers related to M2 macrophage activation, such as CD16, CD163, MerTK, CD206, AMAC1 and CD200R1 [23][24][25][26][27], was upregulated in cmMTB-conditioned cells ( Figure 1B, Supplementary information, Figure S1B). Similarly, the expression of CCR2 and CCR5 chemokine receptors was higher in the presence of cmMTB, supporting the acquisition of the M2 program (Supplementary information, Figure S1C) [28,29].…”
Section: Differentiation Of Human Monocytes Towards An M2-like Activamentioning
confidence: 96%
“…Recent studies by Zizzo et al [25,69] suggested a strict correlation between systemic lupus erythematosus (SLE) disease severity and the activation of an M2-like macrophage characterized by CD163 and MerTK expression during the monocyte-to-macrophage differentiation. Expanding upon our previous observation that the monocyte compartment becomes perturbed in TB patients [18], we now report that the CD163 + MerTK + pSTAT3 + signature accompanies the expansion of the CD16 + monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How Axl and Mer are activated in this macrophage population in the context of an inflammatory response remains to be determined, however. The TAM agonists Pros1 and Gas6 are expressed by murine and human macrophages (43,44); thus, it is possible that TAM signaling in macrophages is triggered in an autocrine manner. In addition, we have recently demonstrated that T-cell-derived Pros1 constitutes a relevant in vivo source of this anti-inflammatory TAM ligand (45).…”
Section: Discussionmentioning
confidence: 99%
“…When expressed by monocytes and granulocytes, these receptors (and in particular MerTK) can also mediate the phagocytosis of apoptotic cells [7], which is fundamental in order to remove dead cells without triggering inflammation. Several data now exist that underline the importance of MerTK activation in the elimination of potential autoantigens derived by apoptotic cells, in the inhibition of the production of proinflammatory cytokines, and in the prevention of the expansion of autoreactive lymphocytes [8][9][10]. The functional impairment of MerTK promotes not only autoimmunity but also atherosclerosis, while its overexpression is linked to poor prognosis in cancer [11].…”
mentioning
confidence: 99%